Enhancing the Entrepreneurial Capability of Housewives in Argopuro Sawahan through Training on Kimchi Production and Cost of Goods Sold Calculation - Gesti Memarista; Lila Gestanti; Pauline Tanza (Civiliza Publishing, 2026)
Household entrepreneurs, especially housewives looking to supplement their income for their families, have new business options due to Indonesia's rising demand for Korean food. Unfortunately, many would-be business owners don't know enough about product costing, leading to poor pricing strategies and low profitability. By offering hands-on instruction in kimchi production and cost of goods sold (COGS) calculation, this community service initiative sought to enhance the entrepreneurial potential of twenty housewives in Argopuro Sawahan. The community needs assessment, program design, practical kimchi production instruction, and financial literacy training centered on COGS calculation using the full-costing method, which comprises the four steps of the program's participatory approach. The results showed that participants' understanding of kimchi manufacturing, identification of production cost components, computation of COGS, and determination of suitable selling prices had significantly improved by 156.42%. Additionally, participants showed greater confidence in starting food companies from home. Technical food production skills were successfully integrated with fundamental financial management to enhance entrepreneurial competencies and promote long-term household economic empowerment. The program emphasizes the importance of combining financial literacy with hands-on entrepreneurship training to enhance the competitiveness of micro and small businesses.